Sinergi Kementerian Luar Negeri dan Kementerian Pertahanan dalam Politik Luar Negeri Indonesia - Agus Subagyo; Yusep Ginanjar (Universitas Diponegoro, 2020)
In the history of Indonesia’s foreign policy, there are often differences in attitudes between the Ministry of Foreign Affairs and the Ministry of Defense in responding to international issues. The Ministry of Defense seems to act unilaterally and pays little attention to the Ministry of Foreign Affairs in expressing attitudes and views regarding Indonesia’s foreign policy. There are disagreements between two ministries that cause polemics and pros and cons in government circles which eventually evaporate in public space. This paper analyzes the lack of synergy between the Ministry of Defense and the Ministry of Foreign Affairs in addressing international problems, which seem to work independently. This paper argues that a one-door policy in Indonesian foreign policy is needed, where the Ministry of Foreign Affairs must be positioned as the only door in the formulation and implementation of foreign policy, which the Ministry of Defense must submit to and comply with and synergy with the Ministry of Foreign Affairs in foreign policy issues.